A protease-resistant Escherichia coli asparaginase with outstanding stability and enhanced anti-leukaemic activity in vitro. Issue 1 (December 2017) - Maggi, Maristella; Mittelman, Steven; Parmentier, Jean; Colombo, Giorgio; Meli, Massimiliano; Whitmire, Jeannette; Merrell, D.; Whitelegge, Julian; Scotti, Claudia
Abstract L-Asparaginases (ASNases) have been used as first line drugs for paediatric Acute Lymphoblastic Leukaemia (ALL) treatment for more than 40 years. Both theEscherichia coli (EcAII) andErwinia chrysanthemi (ErAII) type II ASNases currently used in the clinics are characterized by highin vivo instability, short half-life and the requirement of several administrations to obtain a pharmacologically active concentration. Moreover, they are sensitive to proteases (cathepsin B and asparagine endopeptidase) that are over-expressed by resistant leukaemia lymphoblasts, thereby impairing drug activity and pharmacokinetics. Herein, we present the biochemical, structural andin vitro antiproliferative characterization of a new EcAII variant, N24S. The mutant shows completely preserved asparaginase and glutaminase activities, long-term storage stability, improved thermal parameters, and outstanding resistance to proteases derived from leukaemia cells. Structural analysis demonstrates a modification in the hydrogen bond network related to residue 24, while Normal Mode-based geometric Simulation and Molecular Dynamics predict a general rigidification of the monomer as compared to wild-type. These improved features render N24S a potential alternative treatment to reduce the number of drug administrationsin vivo and to successfully address one of the major current challenges of ALL treatment: spontaneous, protease-dependent and immunological inactivation of ASNase.